The prevalence of depression in patients with lumbar degenerative disk disease: A systematic review and meta-analysis - Konstantin Li; Auyeskhan Dzhumabekov; Yermek Dyusembekov; Ardak Nurbakyt; Natalya Glushkova (PLoS ONE, 2025)
Background Lumbar degenerative disc disease (DDD) is a prevalent musculoskeletal disorder characterized by significant pain, disability, and reduced quality of life. Depression frequently coexists with chronic pain conditions, intensifying symptoms and complicating management. Despite its clinical relevance, the prevalence of depression specifically among patients with lumbar DDD remains inadequately understood. Aim This systematic review and meta-analysis aimed to assess the prevalence of depression among patients with lumbar DDD and to identify potential sources of heterogeneity. Methods A comprehensive literature search was conducted using PubMed, Web of Science, ScienceDirect, Academic Search Complete, and Google Scholar to identify relevant studies published between 2015 and 2022. Studies reporting the prevalence of depression among patients with lumbar DDD were included in the analysis. Pooled prevalence estimates were calculated using random-effects models, and subgroup analyses were performed to investigate sources of heterogeneity. Results Seven studies met the inclusion criteria, encompassing 3485 patients with lumbar DDD. The pooled prevalence of depression was estimated at 20.19% (95% CI 8.94–39.46%). Subgroup analyses revealed significant variations in prevalence estimates across different geographic regions and assessment tools. Sensitivity analyses confirmed the robustness of the findings, while meta-regression analyses did not identify significant associations between prevalence rates and factors such as age or year of publication. Conclusions This study highlights a substantial burden of depression among patients with lumbar DDD, emphasizing the need for comprehensive mental health assessment and management in this population. The findings contribute to a better understanding of the psychological comorbidities associated with lumbar DDD and have implications for clinical practice and future research.